Breeding season habitat selection by ferruginous pygmy owls glaucidium brasilianum in central Argentina - Campioni, Letizia (2013)
Capsule The presence of Ferruginous Pygmy Owls Glaucidium brasilianum breeding in the xerophytic forest of Caldén Prosopis caldenia in central Argentina was slightly affected by forest maturity but neither by the structure of vegetation strata at the micro-habitat scale, nor by forest composition (mosaic of forest-grassland or shrubland) or proximity of water bodies at the macro-habitat scale. Aims To assess the habitat characteristics selected by Ferruginous Pygmy Owls during the breeding season. Methods Random transects were performed across a portion of the Luro Natural Reserve by broadcasting Ferruginous Pygmy Owl calls. Locations along these transects were used to carry out a presence/absence habitat analysis at micro-and macro-habitat levels. Results Ferruginous Pygmy Owls were found in the majority of sampled locations. However, their presence was not associated with the vegetation structure and composition around sampled locations. Model outputs suggested similarity among presence and absence locations at both spatial scales, though owls showed a slight preference for areas with older trees and higher edge-density values. Conclusion The Ferruginous Pygmy Owl was more abundant than previously thought in the Caldén xerophytic forest, emphasizing the habitat's conservation importance, particularly because of the land-use changes that the La Pampa region is experiencing (e.g. forest exploitation). © 2013 British Trust for Ornithology.